Y chromosome effect on prenatal live weight growth of laboratory minipigs - Shatokhin Kirill; Nikitin Sergey; Knyazev Sergey; Zaporozhets Vera; Pashkovskiy Sergey (E3S Web of Conferences, 2020)
This paper describes the results of the influence of Y-chromosome gene complex on pre- and postnatal growth of piglets of laboratory mini-pigs ICG SB RAS. Breeding group includes four genealogical lines of boars united by a successive father-son relationship. Three lines: MS2853, MS2987, and VTN300 inherited their Y chromosomes from boars of Vietnamese-South Asian breed. The fourth line (LNDR07) received Y chromosome from the Landrace boar. This study revealed that all three lines of boars carrying Asian Y chromosome did not differ in weight of newborn offspring, while the weight and, correspondingly, prenatal growth of newborns of boars carrying European Y chromosome were statistically significantly less. Thus, at this stage of research, there is reason to believe that the selection group of mini-pigs ICG SB RAS contains polymorphism in the complex of Y-chromosome genes involved in the control of prenatal growth process. An assumption was considered that growth retardation during prenatal and early postnatal periods, as well as an increased proportion of culled offspring of boars carrying European Y chromosome can be caused by poor compatibility of its gene complex with the allele pool inherited from the mini pigs ICG SB RAS from Vietnamese breed.